The potential of incorporating norm-critical design objects as a pedagogical tool in sociology courses - Isaksson, Anna (Frontiers in Sociology, 2024)
Previous research has raised challenges in teaching gender theory in sociology courses. While many students appreciate such theories, some students resist sociological approaches to gender, sexualities, and social inequalities. There is a growing body of research that has recognized and explored pedagogical tools aiming to help students engage with sociological insights and concepts related to gender. However, more studies and pedagogical frameworks are needed to guide higher education teachers. Consequently, this perspective article aims to introduce and present how norm-critical design objects can be used as a pedagogical tool to enhance student learning and engagement. The article demonstrates how such objects have been incorporated into sociology courses and provides a springboard for reflective, thorough, and problematizing approaches to gender issues in sociology. Further, the article encourages a broader sociological discussion about the potential of using norm-critical design objects in sociology courses.